IMPLEMENTASI PEMANFAATAN TEKNOLOGI IOT DAN BLOCKCHAIN PADA SISTEM LOGISTIK CABE - Sofyan asaury; Moch. Lutfi (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
This research aims to develop a chili logistics system that utilizes the Internet of Things (IoT) and blockchain technology. This system is designed to improve the efficiency and transparency of the chili logistics process from collection, delivery, to distribution using a smartphone. IoT is used to monitor environmental conditions for storing and transporting chilies, such as temperature and humidity, so as to prevent damage to chilies. Meanwhile, blockchain technology is used to optimize transparency and security in the chili logistics process by ensuring the authenticity of products and data recorded on the blockchain. The methodology used in this study uses the prototyping method. Implementation of IoT technology with an average temperature of 30 ֯ C and 40% humidity. Also, the blockchain system in the chili logistics system can be an effective solution in increasing efficiency, transparency and security in sending chilies.